557Outcomes of Indigenous multifetal and singleton pregnancies: complications, medical care, birth experience and infant health. (2nd September 2021) - Gibberd, Alison; Tyler, Jessica; Preen, David; Falster, Kathleen; Hanly, Mark; Clarke, Marilyn; McNamara, Bridgette; Eades, Sandra
Abstract: Background: Perinatal outcomes for singleton pregnancies are poorer, on average, for Aboriginal people than non-Aboriginal people, but little is known about Aboriginal multifetal pregnancies. Yet multifetal pregnancies and births are often more complicated and have poorer outcomes than singleton pregnancies. We describe the pregnancies, births and outcomes for Aboriginal twins born in Western Australia (WA) and New South Wales (NSW) with comparisons to Aboriginal singletons (WA and NSW) and non-Aboriginal births (NSW). Methods: Whole-population birth and hospital records were linked for births during 2000-2013 (WA) and 2002-2008 (NSW). Descriptive statistics are reported for demographics, maternal health, pregnancy complications, births and infant outcomes. Results: Pregnancy complications were more common among mothers of Aboriginal twins than Aboriginal singletons (e.g. 17% of mothers of WA twins had hypertension/pre-eclampsia/eclampsia vs 8% for singletons) but similar to mothers of NSW non-Aboriginal twins. Most Aboriginal twins were born in principal referral, women's or large public hospitals. The hospitals were often far from the mother's home (e.g. 31% of mothers of WA Aboriginal twins gave birth at hospitals located >3 hours by road from their home). Outcomes were worse for Aboriginal liveborn twins than Aboriginal singletons and non-Aboriginal twins (e.g. 58% of NSW Aboriginal twins were preterm versus 9% of Aboriginal singletons and 49% non-Aboriginal twins). Conclusions: Mothers of Aboriginal twins faced significant challenges during the pregnancy, birth and the postnatal period in hospital. Key messages: In addition to accessible specialist medical care, these mothers may need extra practical and psychosocial support throughout their journey.